DEVELOPMENT OFBIOTECHNOLOGY TEACHING MATERIALS WITH ENVIRONMENTAL BIOTECHNOLOGY CONCEPT BASED ON BIOLOGICAL EDUCATION FKIP UR STUDENT RESEARCH (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This research aims to determine the application of various bio-activator to the vegetable and leaf waste to produce compost anddeveloping the biotechnology teaching materials with environmental biotechnology concept based on biological education FKIP UR student research.The research was conducted from April to November 2014. This study consisted of two stages, namely composting stage of vegetable waste and leaves with a bio-activator EM-4, Orgadec and Acticomp and material development stage from the research results. Composting stage using the True-Experimental Research with the RAL that consisting of 4 treatments and 3 replications. Research procedure consisted of four stages, namely preparation of tools and materials, the implementation of composting stage, observation of the composting process and the completion stage. Parameters in this research is the texture, length of composting, C/N ratio of compost. Data were analyzed quantitatively and qualitatively. The second stage, development of teaching materials referring to the R & D research approaches by using model ADDIE. The instrument that used for data collection are sheets of validation. Data were analyzed descriptively. The results showed that Acticomp bio-activator is the best bio-activator to produce compost from vegetable waste and leaves. Results of the research can be developed as a teaching material on the concept of environmental biotechnology in Biotechnology subjects.Keywords: teaching material, environmental biotechnology , based on research